Neurocognitive functioning and symptoms across levels of collision and contact in male high school athletes. Issue 8 (27th April 2022) - Oldham, Jessie R.; Howell, David; Lanois, Corey; Berkner, Paul; Iverson, Grant L.; Mannix, Rebekah; Meehan, William
Abstract : Objective: We sought to determine whether male collision sport athletes perform worse on computerised neurocognitive assessments and report higher symptom burdens than athletes in contact (but not collision) sports and athletes in non-contact sports. Methods: This cross-sectional study used data collected by the Massachusetts Concussion Management Coalition on high school boys who underwent computerised neurocognitive testing between 2009 and 2018. We divided sports participation in three different sport types: (1) collision, (2) contact, non-collision and (3) non-contact. Our outcomes included the four computerised neurocognitive composite scores (verbal memory, visual memory, visual motor speed and reaction time) and the total symptom score. The independent variable was sport type (collision, contact, non-contact), adjusted for age, concussion history and comorbidities. Results: Of the 92 979 athletes (age: 15.59±2.08 years) included in our study, collision sport athletes performed minimally but significantly worse than other athletes on neurocognitive composite scores (verbal memory: β=−1.64, 95% CI −1.85 to –1.44; visual memory: β=−1.87, 95% CI −2.14 to –1.60; visual motor speed: β=−2.12, 95% CI −2.26 to –1.97; reaction time: β=0.02, 95% CI 0.02 to 0.02). Collision and contact sport athletes also had slightly but significantly lower total symptom scores (collision: 3.99±7.17; contact: 3.78±6.81; non-contact: 4.32±7.51, p<0.001, η 2 =0.001) than non-contact sport athletes. Conclusion: There are minimal observed differences in performance on neurocognitive assessments between collision sport, contact sport and non-contact sport athletes. The repetitive subconcussive head impacts associated with collision sport participation do not appear to negatively affect self-reported symptoms or neurocognitive functioning in current youth athletes.